Stress - induced expression of IPT gene in transgenic wheat reduces grain yield penalty under drought - Beznec, Ailin (2021)
Fil: Beznec, Ailin. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Genética Edwald A. Favret. Buenos Aires, Argentina.